Historic Preservation: A Multilayered Inclusive Approach Honoring Immigrants Past and Present. Issue 2 (May 2018) - Rodgers, Diane M.; Sosa, Lucy; Petersen, Jessica
Social justice and housing issues are clearly an area of concern for sociologists, yet preservation of older homes and buildings may seem to be the very antithesis, evoking images of homes of the nation's elite or neighborhood gentrification by the white upper middle class. Often preserved historic sites do not fully represent members of the community, past or present. Despite increasing efforts at inclusion, marginalization of groups can still be found in the practice of historic preservation. The ideology and practice of preserving chosen heritage sites and buildings and protecting them from destruction or deterioration offer sociologists a unique window into social inequalities. In this article, we explore the intricacies of preserving the buildings and heritage of a former Finntown, a once thriving community of Finnish-American working-class immigrants and now home to a sizable population of Latino working-class immigrants. Inclusive, multilayered historic preservation can be a source of social justice if honoring the past does not sacrifice the needs of marginalized groups in the present.